Students' Perception of Peer-teaching Method in Training Teaching Skills of Prospective Elementary School Teachers - Prihantini; Ranu Sudarmansyah (PT Inovasi Pratama Internasional, 2024)
This study explores students' responses to how the peer teaching method in microteaching lectures can provide teaching skills to become elementary school teachers. The research applied a quantitative descriptive method by analyzing questionnaire instruments distributed to 35 elementary school teacher education students who took microteaching courses in the fourth semester. Data collection used a closed-ended questionnaire instrument and focus group discussions to identify teaching skills that are still needed by students to be trained through peer teaching. The results of the data analysis showed that the average student perception of peer-teaching reached an average of > 4 (figure 1) out of 12 questionnaire questions. This figure indicates a good category. The results of the focus group discussion obtained data that what still needs to be trained through peer teaching is adjusting learning strategies to the learning material and the background of students and eliminating the fear of making mistakes that make them insecure in front of their peers. Based on the results of data analysis, it is concluded that students' perceptions are good about peer teaching and can help them equip teaching skills as prospective elementary school teachers. However, it is still necessary to add skill training through peer teaching about adjusting learning strategies to the material being taught and eliminating self-confidence. From the findings of this study, it is suggested that to prepare the competence of elementary school teachers through micro-teaching courses, the peer teaching method needs to be maintained but it needs to be added to the content of skills that are still needed by students, namely preparing lesson plans.